Students' Perceptions of Using Manual Typewriters and Rapid Typing Application in Basic Typing Course - Dheanda Maurizta Chairunnisa; Gita Hindrawati; Linda Aprillianti; Rifka Uzma Wardati; Alya Hasna Fauziyyah; Naya Yasinta Ramadhanti (Politeknik Negeri Semarang, 2026)
Advances in digital technology have brought about change in various aspects of education, including the teaching of typing skills at vocational colleges. This study aims to determine students perceptions of the use of manual typewriters and the Rapid Typing application in basic typing instruction, as well as to compare the effectiveness of the two. The research method used was quantitative descriptive, employing data collection through the distribution of questionnaires to first-year students in the D3 Business Administration Program at the State Polytechnic of Semarang. Data analysis utilized the Likert scale and the Three-Box Method. The result indicated that students perception regarding the use of manual typewriters fall into the moderate category, while the use of the Rapid Typing application falls into the high category. Furthermore, the comparison results indicate that students tend to prefer the Rapid Typing application over manual typewriters because it is considered more effective, engaging, interactive, and user-friendly in enhancing ten-finger typing skills. The use of the Rapid Typing application is also deemed more aligned with technological advancements and modern learning needs. Thus, the Rapid Typing application can serve as an educational tool that optimally supports the improvement of students’ typing skills.